2008
DOI: 10.1016/j.jcf.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported involvement of family members in the care of adults with CF

Abstract: The depth of commitment required of families of children with CF has been well documented for decades. Our results suggest that the responsibilities of family members diminish only moderately as those with CF reach adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…The ‘parent‐as‐partner’ role supports the ‘lay carer’ role described by parents themselves (Lowton 2002), the ‘shared care’ role of parents and young people in home administration of treatment (Badlan 2006) and is similar to the continuing role of many parents in ‘prompting’ older offspring with CF to take their medication, even when they are no longer co‐resident (McGuffie et al. 2008).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The ‘parent‐as‐partner’ role supports the ‘lay carer’ role described by parents themselves (Lowton 2002), the ‘shared care’ role of parents and young people in home administration of treatment (Badlan 2006) and is similar to the continuing role of many parents in ‘prompting’ older offspring with CF to take their medication, even when they are no longer co‐resident (McGuffie et al. 2008).…”
Section: Discussionmentioning
confidence: 91%
“…2000). Most young people require multiple complex treatments and care for deteriorating health and the advent of CF‐related conditions; for patient comfort and to reduce hospital admissions, these continue to be administered in the home by family members wherever possible, requiring knowledge, skill, time and energy (McGuffie et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They endorsed a simultaneous desire for independence with a need to have a safety net, most often provided through their caregivers. Such concepts are not surprising; in fact, many adults with CF continue to report significant caregiver involvement in their daily lives and routines …”
Section: Discussionmentioning
confidence: 99%
“…Lowton (2002) found that lay carers routinely performed tasks for adults with CF that were once performed by nurses such as helping to administer intravenous antibiotics when given as home treatment. McGuffie et al (2008) found similar roles performed by families of adults with CF and other daily tasks such collecting prescriptions, cleaning nebulisers and assisting with physiotherapy. Whilst the findings we describe in the current paper are consistent with these studies, we also found that adults with CF utilised a range of other supports; these were not purely to assist with the demands of medical treatments but extended also to assistance with daily living tasks (shopping, cooking, gardening etc.)…”
Section: Cystic Fibrosismentioning
confidence: 66%